A TESSERACT ON THE XPOLAR (BIPOLAR) SPECTRUM – AN HEURISTIC FOR THE CLASSIFICATION OF AFFECTIVE ILLNESS - James Le Bas (LIFE: International Journal of Health and Life-Sciences, 2025)
Psychiatric classification has not kept pace with advances in neuroscience; diagnostic models are stuck in the era of Kraepelin, and while diagnoses have slowly become more reliable, some are invalid. We need models where nodes (categories) complement dimensions – for example hypomania occurring on an axis of excitement and depression on an axis of fight, flight and freeze (FFFS) (melancholia may in fact be an evolutionary ‘freeze’). The Tesseract is one recent attempt at spatial nosology; it makes use of Gray’s dimensions of behavioural approach (BAS), behavioural inhibition (BIS) and the FFFS. The addition of a RAGE axis allows for the incorporation of mania and creates a four-dimensional hypercube for syndromal classification. This marries with a mapping of syndromes into ACTIVATION or INHIBITION. Mixed syndromes are allowed for – an example being psychotic depression. The collection of syndromes into disorders is depicted in the xPolar spectrum, being based on the bipolar phenotype (Fear, anxiety and anxiety syndromes, self-esteem disturbance, striving for goals, depression and addictive tendencies – FASSDA). There may have been progressive adaptations in the spectrum over evolutionary time; the addictive object for most being the ‘social high’. A path for the escalation of positive and negative symptoms in schizophrenia will be depicted as an outlier of the affective spectrum. An allostatic point where positive ‘asymmetries’ become ‘supersymmetries’ (salience) is depicted, as is another where dopamine falls, and atypical depression supervenes in the ‘hypernormal’ self – in which observation is narrowed to avoid perceptual overload. And the cycle starts again.